Feasibility of the application of the doctrine of judicial precedent in civil and shariah courts - Ahmed, Kyaw Hla Win @ Md Hassan; Mikail, Sa'id Adekunle; Arifin, Mahamad; Ali Mohamed, Ashgar Ali (LexisNexis, 2013)
The doctrine of judicial precedent plays an empirical role in the common law system, but it only has persuasive value in European countries which are practicing the civil legal system. Moreover, it has not been recognised as having a binding force in the Islamic legal system and thus each case has to be decided based on its own merits and previous decisions were merely considered as guidance for the future decision. This position is still being maintained by some countries such as Malaysia and Saudi Arabia. In Pakistan and Nigeria, however, the doctrine of judicial precedent is followed. Due to this contradiction among the Shariah legal system in various countries, as a result, a question arises relating to the feasibility of the application of the doctrine of judicial precedent in Shariah Courts needs thorough study. Accordingly, in this paper, the factual nature of the judicial precedents in both civil and Shariah legal systems have been examined comparatively in some detail with reference to countries such as England, Malaysia, Nigeria and Pakistan. This paper points out that the doctrine of stare decisis and judicial precedent can be applied in the Shariah Courts system as guiding precedents but not as binding precedents since it is allowed in Shariah to take guidance from previous decisions and there is no express prohibition in Shariah on them.